PENERAPAN COOPERATIVE LEARNING TIPE JIGSAW UNTUK MENINGKATKAN PEMAHAMAN DAN KETERAMPILAN MAHASISWA - Setiani, Rediana (Fakultas Ekonomi, Universitas Negeri Semarang, 2009)
The objectives of this study are: (1) to improve studentsÃ¢â‚¬â„¢ understanding in Accounting Computer subject mahasiswa pada mata kuliah Komputer Akuntansi, (2) to improve studentsÃ¢â‚¬â„¢ skills in Accounting Computer subject. The subject of this research is accounting students of education program that take accounting computer subject. This research is class action research consists ofÃ‚Â 3 cycles. The given action in the first cycle according to the result of beginning reflection. In every cycle consists of 4 stages that are planning, actuating, observation, and reflection. This research reached standardized indicator that 70% students have minimum score that was 71 (B). It showed that the application of cooperative learning jigsaw type can improve the studentsÃ¢â‚¬â„¢ ability in a computer accounting subject. Ã‚Â Key Words : Cooperative Learning, Jigsaw, the studentsÃ¢â‚¬â„¢ understanding, creativity